(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the importance of pharmaceutical assistance in health care within primary care, making it possible to understand the primary role of the pharmacist in care centered on the individual and the collective. This is a descriptive, integrative literature review type study, where scientific publications indexed in the online databases Virtual Health Library – VHL (Medline, IBECS and LILACS) and SCIELO from 2016 to 2021 were searched. 167 articles were retrieved, being 80 results from the MEDLINE database, 46 from LILACS, 14 from IBECS, 27 from SCIELO. After reading the titles and abstracts, 20 articles were selected. He noted that the implementation of pharmaceutical care (PA) is seen as one of the tools for strengthening within the Unified Health System (SUS). This is directly linked to the development of its participatory management in the system, which I designate ensures access to medicines and integral therapeutic care. The inclusion of the pharmacist in this context positively impacts the health of the population when he works alongside the population, caring for and promoting health, carrying out strategies aimed at the well-being of the individual and the family.